1978
DOI: 10.1073/pnas.75.12.5879
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of albumin production rates and albumin mRNA levels in livers of normal, diabetic, and insulin-treated diabetic rats.

Abstract: We have studied the effects of alioxan-induced diabetes and subsequent insulin replacement on albumin and total hepatic protein synthesis. Diabetes resulted in a reduction to approximately 20% of normal in albumin synthesis relative to the rate of total protein synthesis in vivo and a reduction to 10% in the absolute rate of albumin secretion by perfused livers. In contrast, the synthesis of total secretory protein and retained hepatic protein was affected to a lesser extent by diabetes.Treatment of diabetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
1
2

Year Published

1985
1985
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(75 citation statements)
references
References 30 publications
5
67
1
2
Order By: Relevance
“…3). On the other hand, previous studies showed that albumin mRNA concentration and albumin synthesis are increased by insulin (35)(36)(37)(38). Therefore, the albumin improvement effect by dietary MCT may also be attributable to direct albumin mRNA expression through increased plasma insulin concentration.…”
Section: Discussionmentioning
confidence: 85%
“…3). On the other hand, previous studies showed that albumin mRNA concentration and albumin synthesis are increased by insulin (35)(36)(37)(38). Therefore, the albumin improvement effect by dietary MCT may also be attributable to direct albumin mRNA expression through increased plasma insulin concentration.…”
Section: Discussionmentioning
confidence: 85%
“…A correlation has been shown in rats between pancreatic proinsulin mRNA concentration and rates of in vivo incorporation of [3Hjleucine into proinsulin, showing comparable ability to assess rates of insulin biosynthesis (16,17). A correlation between tissue mRNA levels and protein synthetic rates also has been shown for other protein systems in vitro (23,24) and in vivo (25,26).…”
Section: Introductionmentioning
confidence: 79%
“…Albumin synthesis Albumin is synthesized in liver and represents from 12% to 18% of the total protein synthesized by the liver in rat hepatocytes (Peavy et al, 1978). Increased albumin synthesis was found in Iberian compared with Landrace hepatocytes (58%, P < 0.05; Figure 3b).…”
Section: I/g Ratiomentioning
confidence: 96%